Enzymes hosted in redox-active ionically cross-linked polyelectrolyte networks enable more efficient biofuel cells. Issue 20 (5th May 2021) - Coria-Oriundo, Lucy L.; Cortez, M. Lorena; Azzaroni, Omar; Battaglini, Fernando
Abstract : Self-assembled nanobiocatalyst. Phosphate-mediated cross-linking of redox polyelectrolytes and glucose oxidase leads to self-assembled nanostructures with higher output power density per mol of mediator, thus enabling more efficient biofuel cells. Abstract : Redox mediators are pivotal players in the electron transfer process between enzymes and electrodes. We present an alternative approach for redox mediation based on branched polyethyleneimine (BPEI) modified with an osmium complex. This redox polyelectrolyte is crosslinked with phosphate to produce colloidal particles with a diameter of ca. 1 μm, which, combined with glucose oxidase (GOx), can form electroactive assemblies through either layer by layer assembly (LbL) or one-pot drop-casting (OPDC). The addition of NaCl to these colloidal systems induces the formation of films that otherwise poorly grow, presenting an outstanding catalytic current. The system was tested as a bioanode delivering a power output of 148 μW per nmol of mediator. These results are explained in terms of the interactions of the ions with the polyelectrolyte and represent a new route for the development of bioelectrochemical devices involving redox mediators and enzymes.